TOWARDS MSME SUSTAINABILITY: THE ROLE OF ENTREPRENEURIAL COMPETENCE, INFORMATION TECHNOLOGY AND ACCESS TO CAPITAL - Yahya, Rizki Fakhrul; Sari, Wilda; Mayasafitri, Rina (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
The primary aim of this study was to investigate how entrepreneurial abilities, IT, and financial backing influence the long-term survival of small and medium-sized businesses in Pontianak City. In order to conduct this study, a quantitative approach was utilised, with a survey used as the means of gathering data. The focus group included all SMEs in Pontianak City, and a total of 156 businesses were chosen through purposive selection. Data analysis was carried out using multiple regression analysis, with the help of SPSS software. The results revealed that entrepreneurial skills, IT, and access to funding all had a significant and beneficial impact on the resilience of SMEs. Additionally, having access to financial resources was singled out as a crucial element in fostering the growth and competitiveness of SMEs. This study has practical implications for policymakers and business owners seeking to create an enabling environment for the advancement and sustained success of SMEs in the digital age.